Engineering yeast for utilization of alternative feedstocks. (October 2018) - Yaguchi, Allison; Spagnuolo, Michael; Blenner, Mark
Graphical abstract: Highlights: Xylose, acetate, aromatics, and wastes are promising alternative substrates. Alternative substrates can have economic and metabolic benefits compared to glucose. Non-conventional organisms are often better suited for bioproduction. Rapid genetic engineering tool development has tamed non-conventional organisms. Abstract : Realizing the economic benefits of alternative substrates for commodity chemical bioproduction typically requires significant metabolic engineering of common model organisms, such as Saccharomyces cerevisiae . A growing toolkit is enabling engineering of non-conventional yeast that have robust native metabolism for xylose, acetate, aromatics, and waste lipids. Scheffersomyces stipitis was engineered to produce itaconic acid from xylose. Yarrowia lipolytica produced lipids from dilute acetate at over 100 g/L. Cutaneotrichosporon oleaginosus was engineered to produce omega-3 fatty acids and recently was shown to accumulate nearly 70% lipids when grown on aromatics as a carbon source. Further improvement to toolkits for genetic engineering of non-conventional yeast will enable future development of alternative substrate conversion to biochemicals.